1996
DOI: 10.1557/proc-462-45
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Degree of Polymerization of Cellulose in Ligneous Papers

Abstract: In the past, many attempts have been made to determine the degree of polymerization (DP) of cellulose in ligneous pulps or papers. Frequently, the methods employed caused severe depolymerization of the cellulose.The present paper provides a detailed procedure of DP determination of cellulose for both lignin-free and ligneous papers. The proposed method is based on viscosity measurements of cadoxen solutions of cellulose. Prior to dissolution in cadoxen, ligneous samples are partially delignified by a modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…However, complete removal of the lignin was avoided to minimize the damage to the cellulose 37 . The presence of the remaining lignin is in part responsible for the lower DP values determined for the mechanical pulps, particularly for the spruce samples 38 . Another reason for the lower DP values for the mechanical pulps is the presence of a larger amount of hemicellulose in these pulps as compared to the kraft ones.…”
Section: Resultsmentioning
confidence: 98%
“…However, complete removal of the lignin was avoided to minimize the damage to the cellulose 37 . The presence of the remaining lignin is in part responsible for the lower DP values determined for the mechanical pulps, particularly for the spruce samples 38 . Another reason for the lower DP values for the mechanical pulps is the presence of a larger amount of hemicellulose in these pulps as compared to the kraft ones.…”
Section: Resultsmentioning
confidence: 98%
“…The delignification of paper was performed according to the literature [ 12 ]. The reaction mixture was prepared from 40 mL of distilled water, 0.125 mL of acetic acid (CH 3 COOH, ≥99.8%, puriss p.a.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to viscometric determination of average DP v , attempts were made to partially remove the lignin by chlorite treatment to allow subsequent dissolution of paper made from high-yield pulps [ 6 , 12 ]. It was reported that under the conditions of a modified chlorite method, significant depolymerization of cellulose is prevented, enabling viscometric determination of average DP v in cadoxen solution of cellulose [ 12 ]. Viscometry represents a robust, rapid, inexpensive, and efficient technique, but under certain conditions, such as delignification, it can provide data that are subject to systematic error, making it is necessary to compare the results with M w determinations with SEC [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mass of cellulose, as determined by viscosity tests or gel permeation chromatography, is yet another way to quantify effects of paper deacidification (Eldin and Fahmy 1994;Kaminska and Burgess 1994;Liers and Vogelsanger 1997;Dupont et al 2002;Kolar and Strlič 2004;Sundholm and Tahvanainen 2004;Ipert et al 2006;Sequeira et al 2006;Henniges and Potthast 2008). Progress has been made in being able to evaluate cellulose DP even in samples that contain substantial amounts of lignin, as is the case for most newspaper and magazine samples (Kaminska 1997).…”
Section: Cellulose Degree Of Polymerization (Dp)mentioning
confidence: 99%